2013
DOI: 10.1002/ajhb.22385
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the infant BMI peak: Sex differences, birth year cohort effects, association with concurrent adiposity, and heritability

Abstract: Objectives To characterize an early trait in the BMI-for-age curve, the infant BMI peak. Methods BMI-for-age curves were produced for 747 non-Hispanic, white Fels Longitudinal Study participants, from which individual age (AgePeak) and BMI (BMIPeak) at maximum infant BMI were estimated. Multivariable general linear regression was used to examine the effects of sex and birth year cohort (1929–1950, 1951–1970, and 1971–2010) on AgePeak and BMIPeak, with associations between BMIPeak and concurrent sum of four s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 58 publications
3
22
3
Order By: Relevance
“…In fully adjusted models in the latter study, a two standard deviation (SD) increase in age at peak was associated with a 1.58 % change in BMI at age 31 years and a two SD increase in magnitude of peak with a 4.65 % change. This finding is seemingly paradoxical to the observation of a secular trend toward earlier and lower peak as the environment has become more obesogenic (Johnson et al 2013b). Changes in childhood BMI often reflect changes in fat-free mass more so than fat mass (Demerath et al 2006), so it is not unreasonable to hypothesise that the positive infant peak-adulthood obesity association is driven by reduced fat-free mass in adults who experienced early and/or low peak.…”
Section: Infancycontrasting
confidence: 47%
See 1 more Smart Citation
“…In fully adjusted models in the latter study, a two standard deviation (SD) increase in age at peak was associated with a 1.58 % change in BMI at age 31 years and a two SD increase in magnitude of peak with a 4.65 % change. This finding is seemingly paradoxical to the observation of a secular trend toward earlier and lower peak as the environment has become more obesogenic (Johnson et al 2013b). Changes in childhood BMI often reflect changes in fat-free mass more so than fat mass (Demerath et al 2006), so it is not unreasonable to hypothesise that the positive infant peak-adulthood obesity association is driven by reduced fat-free mass in adults who experienced early and/or low peak.…”
Section: Infancycontrasting
confidence: 47%
“…Nonetheless, like percentage body fat, BMI shows a complex pattern of age-related change that can be summarised by the timing and magnitude of the maximum or peak value in infancy (Johnson et al 2013b). Two studies have reported associations of both later timing and greater magnitude of this infant BMI peak with higher BMI later in life, one study in childhood (Silverwood et al 2009) and one in adulthood (Sovio et al 2014).…”
Section: Infancymentioning
confidence: 99%
“…From birth, BMI increases and reaches a peak around 9 months of age (“infancy peak BMI” or “adiposity peak”), then gradually drops to a low point in the range of 4–6 years old (“adiposity rebound”) [9, 10], and after that continues to rise up through adolescence until adulthood. An alternative promising approach is the use of infancy BMI trajectories (and associated characteristics such as the magnitude and timing of infancy BMI peak), which have been shown by several studies to be predictive of adiposity in children and in adulthood [9, 10, 11, 12, 13].…”
Section: Childhood Obesity: Definition and Epidemiologymentioning
confidence: 99%
“…An alternative promising approach is the use of infancy BMI trajectories (and associated characteristics such as the magnitude and timing of infancy BMI peak), which have been shown by several studies to be predictive of adiposity in children and in adulthood [9, 10, 11, 12, 13]. …”
Section: Childhood Obesity: Definition and Epidemiologymentioning
confidence: 99%
“…The BMI curve typically rises steeply in infancy, peaks just before 1 year, then falls until adiposity rebound at age 4-5 y when it rises again [8]. The advance in developmental age shifts this pattern to the left, with both the age at BMI peak and the age at adiposity rebound getting earlier [9,10], independently of any secular increase in BMI. Because of its shape, the age-shifted curve is slightly lower than the original curve at some ages (Fig.…”
mentioning
confidence: 99%